Lifelong Learning in the System of Higher Education: the State of the Problem and the Strategy of Integrating Educational Activities and Research - A. V. Keller; I. A. Korshunov; N. N. Shirkova; G. N. Suvorov; E. S. Szhenov; S. S. Shadrin; A. A. Orekhov (Высшее образование в России)
The authors of this article consider the current situation of lifelong learning education in leading Russian universities and define some possible strategies for integrating scientific research with educational activities. The empirical bases were: 1) statistical data on the activities of educational institutions of higher education (N = 1180), 2) dataset of monitoring the activities of universities participating in the federal academic leadership programme “Priority-2030”, 3) dataset of a survey of heads of centers for further vocational education in Russian universities (N = 450) as part of the Project “Monitoring of education markets and organizations (MEMO)”. The authors identified strategies for combining scientific and educational activities for lifelong learning programs at universities in the interests of the development of individual consumers, enterprises and branches of the national economy. The authors also found that universities take into account the social needs of society and the preferences of employers, but to a very small extent focus on transforming their scientific results into a new educational product for mass consumers. The significant focus of universities on research activities to a certain extent hinders the development and launch of new education programs, however, it is a group of research universities that demonstrates a higher cost of programs sold. The authors consider, how universities can be focused on working with the population or industry enterprises, integrating the research results into the modules of education programs, and stimulating an increase in the number of teachers combining research and teaching activities, at realizing the third University’s mission and taking into account the research grant volume.